Role of Vitamin A in Preventing Renal Scarring After Acute Pyelonephritis (Iranian Journal of Kidney Diseases, 2011)
Introduction. The role of vitamin A in re-epithelialization of the damaged mucosal surfaces has been documented. The aim of this study was to evaluate the role of vitamin A in preventing renal scaring after acute pyelonephritis in children. Materials and Methods. This clinical trial study was conducted in children with acute pyelonephritis in Mofid Children Hospital (Tehran, Iran). Patients were randomly divided into two groups to receive ceftriaxone and vitamin A or ceftriaxone only. Dimercaptosuccinic acid (DMSA) renal scintigraphy was performed before the start of the treatment and 6 months later. Results were compared for renal scaring between the two groups. Results. Seventy-six patients (11 boys and 65 girls) were enrolled. The mean age was 25 ± 24 months and 54 patients (71.1%) were under 2 years old. The average vitamin A level was 71 ± 24 microg/dL in the treatment group and it was 62 ± 18 µg/dL in the control group.  Baseline DMSA scans were comparable between the two groups in terms of scarring (P = .53), but the second DMSA scans showed a significant change in progression of the renal injury and scaring in the control group compared to those treated with vitamin A as well as antibiotic (P < .001). Conclusions. We found administration of the vitamin A was useful in decreasing the amount of the injury and scarring following the pyelonephritis. Based on our study, vitamin A can be used in conjunction with other treatments in the management of acute pyelonephritis in children.